Senataxin prevents replicative stress induced by the Myc oncogene - Silvia Sberna; Marco Filipuzzi; Nicola Bianchi; Ottavio Croci; Federica Fardella; Chiara Soriani; Sara Rohban; Sara Carnevali; Alessandra Alberta Albertini; Nicola Crosetto; Simona Rodighiero; Arianna Chiesa; et al. (Cell Death and Disease)
Abstract Replicative stress (RS) is emerging as a promising therapeutic target in oncology, yet full exploitation of its potential requires a detailed understanding of the mechanisms and genes involved. Here, we investigated the RNA helicase Senataxin (SETX), an enzyme that resolves RNA-DNA hybrids and R-loops, to address its role in preventing RS by oncogenic Myc. Upon Myc activation, silencing of SETX led to selective engagement of the DNA damage response (DDR) and robust cytotoxicity. Pharmacological dissection of the upstream kinases regulating the DDR uncovered a protective role of the ATR pathway, that once inhibited, boosted SETX driven-DDR. While SETX loss did not lead to a genome-wide increase of R-loops, mechanistic analyses revealed enhanced R-loops localized at DDR-foci and newly replicated genomic loci, compatible with a selective role of SETX in resolving RNA-DNA hybrids to alleviate Myc-induced RS. Genome-wide mapping of DNA double-strand breaks confirmed that SETX silencing exacerbated DNA damage at transcription-replication conflict (TRC) regions at early replicated sites. We propose that SETX prevents Myc-induced TRCs by resolving transcription-associated R-loops that encounter the replisome. The identification of SETX as a genetic liability of oncogenic Myc opens up new therapeutic options against aggressive Myc-driven tumors.